Triphenylamine dyes bearing 5-phenyl-2-(arylthiophen-2-yl)thiazole bridge for dye sensitized solar cells. (March 2021) - Han, Liang; Yu, Huidan; Chen, Qinqin; Lu, Ying; He, Ji; Jiang, Shaoliang
Abstract: Three triphenylamine dyes were synthesized with 5-phenyl-2-(arylthiophen-2-yl)thiazole as π bridge and cyanoacrylic acid as the acceptor. Three dyes differ in the aryl ring binding with the acceptor in the π bridge, which leads to different photophysical properties, molecular planarity, energy level and accordingly the photoelectric conversion efficiency. The insertion of furan and thiophene units in π bridge attain broader absorption spectra and better molecular coplanarity, contributing to the distinct improvement of J SC and hence the photovoltaic performance. On the other hand, the presence of benzene unit raises the LUMO level and increases the drive force for the electron injection into TiO2, which enhance V OC . Among three dyes, dye bearing two thiophene units sensitized DSSC achieves a cell efficiency 6.90% due to better J SC (14.09 mA cm 2 ) and V OC (0.73 V). Highlights: Three triphenylamine dyes with 5-phenyl-2-(arylthiophen-2-yl)thiazole bridge. The presence of furan or two thiophenes in π bridges of three dyes favors J SC . The presence of two benzene in π bridge of three dyes favors V OC . DSSC based on dye bearing two thiophene units achieves a cell efficiency 6.90%.